2021
DOI: 10.48550/arxiv.2103.02995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On groups of units of special and one-relator inverse monoids

Robert D. Gray,
Nik Ruskuc

Abstract: We investigate the groups of units of one-relator and special inverse monoids. These are inverse monoids which are defined by presentations where all the defining relations are of the form r = 1. We develop new approaches for finding presentations for the group of units of a special inverse monoid, and apply these methods to give conditions under which the group admits a presentation with the same number of defining relations as the monoid. In particular our results give sufficient conditions for the group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 21 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…It can be shown that Λ generates the subgroup consisting of all units of M (see [22,Proposition 4.2], for the stronger form here stated see [19,Theorem 1.3]). This subgroup is denoted U (M ), and is called the group of units of M .…”
Section: ) If W ∈ Amentioning
confidence: 99%
See 4 more Smart Citations
“…It can be shown that Λ generates the subgroup consisting of all units of M (see [22,Proposition 4.2], for the stronger form here stated see [19,Theorem 1.3]). This subgroup is denoted U (M ), and is called the group of units of M .…”
Section: ) If W ∈ Amentioning
confidence: 99%
“…In particular, as already proved by Adian [3,Theorem 8], U (M ) is a onerelator group if M is a special one-relation monoid. Although we do not directly study the group of units in this article, we highlight the fact that by contrast, in the inverse case M = Inv A | w = 1 , it need not be the case that U (M ) is a one-relator group; Gray & Ruškuc [19,Theorem 7.1] provide an example in which U (M ) is isomorphic to the free product of two copies of the fundamental group of a surface of genus 2, which is not a one-relator group by [25,Proposition 5.13]. This demonstrates the contrast between special inverse and special "ordinary" monoids.…”
Section: ) If W ∈ Amentioning
confidence: 99%
See 3 more Smart Citations